2005
DOI: 10.1002/pts.687
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and analysis of truck transport vibration levels and damage to packaged tangerines during transit

Abstract: The purpose of this study was to measure the vibration levels in commercial truck shipments in Thailand and observe the effects on packaged fruit. The study measured the vibration levels in two of the most commonly used truck types to ship packaged goods as a function of road condition and vehicle speed. The suspension type on the trailers studied was leaf-spring. The results of damage to packaged tangerine fruit as a function of location in the payload are also presented. The data presented in this study will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 4 publications
2
93
0
5
Order By: Relevance
“…4,6 In the low-frequency range (1-5 Hz), the measured vibration levels were similar to those of other international studies. Lower intensity vibrations were observed in the 10-20 Hz as compared with the recommended levels recommended in the ASTM and ISTA vibration test methods.…”
Section: Truck Vibration Measurementsupporting
confidence: 87%
See 2 more Smart Citations
“…4,6 In the low-frequency range (1-5 Hz), the measured vibration levels were similar to those of other international studies. Lower intensity vibrations were observed in the 10-20 Hz as compared with the recommended levels recommended in the ASTM and ISTA vibration test methods.…”
Section: Truck Vibration Measurementsupporting
confidence: 87%
“…Packaging Technology and Science, 23: 91-100. doi: 10.1002/pts.881, which has been published in final form at http://onlinelibrary.wiley.com/doi/ 10.1002/pts.881/abstract road conditions from rural un-surfaced roads to highways for shipments of fruits in Thailand, it was found that road surface and truck speed played a significant role in the severity of vibration levels and damage to fruits. 6 A similar study conducted using small local trucks and larger tractor-trailer in 10 different regions in Brazil 4 concluded that the truck transport environment showed lower vibration levels in metropolitan areas than interstate highways. This study also noted that acceleration levels increased with lighter loads, bad road conditions and higher speeds.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The first section of the route may follow relatively rough farm roads, followed by secondary gravel or paved routes, primary paved routes and ultimately metropolitan streets. The condition of each of these routes causes specific dynamics and vibrations in the vehicle used, as well as the cargo transported (Timm et al 1996;Jarimopas et al 2005;Steyn et al 2012). Over the years, pavement engineers have developed means of measuring the actual condition or roughness of the road, and thus the road condition can be objectively quantified and described (Sayers, Gillespie 1986;Jarim 1992).…”
mentioning
confidence: 99%
“…Various authors have studied the effects of road conditions on transported agricultural product (O'Brien et al 1969;Chesson and O'Brien 1971;Singh, Singh 1992;Jarimopas et al 2005). The majority of these studies have focused on the dynamic response of the vehicle and agricultural cargo during the transportation process, as well as the effect of parameters such as the road condition, vehicle speed and vehicle components (e.g.…”
mentioning
confidence: 99%